ANALISIS PENDAPATAN DAN PEMASARAN USAHATANI PEPAYA MINI (Carica papaya L.) DI KELURAHAN TERITIP KECAMATAN BALIKPAPAN TIMUR KOTA BALIKPAPAN - Tuti Susanti, Rita Ratini, dan Mariyah (Universitas 17 Agustus 1945 Samarinda, 2014)
This research were to know income of the mini papaya, marketing channels, marketing margin, farmers share, the marketing profit of the mini papaya which were earned by distributors and marketing efficiency in the district of East Balikpapan subdistrict of Balikpapan Regency. This research was conducted from April to June 2013 in the district of East Balikpapan subdistrict of Balikpapan Regency. Total Respondents 37 people as 15 farmer of papaya mini, 8 wholesalers and 14 retailers. The sampling method used purposive sampling and snowball sampling. The analyze used income analysis and marketing analysis. The results of this research that indicated the income amount of papaya mini as Rp 1,182,204,850.00 for scale 0.5 ha and average Rp 78,813,656.67 respondent-1 year-1 or Rp 134,126,685.30 respondent-1ha-1year -1. The marketing channels are used in the research locations in two level channels. Total marketing margin of the papaya mini is Rp 4,500.00 kg-1. Farmers share is 43.75%. The marketing profit of the papaya mini for wholesalers with the average of Rp 983.04 kg-1 and for retailers with the average of Rp 2,736.06 kg-1 and marketing efficiency for wholesalers is 10.33% and for retailers is 3.29%.